2005
DOI: 10.1016/j.immuni.2004.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and Nonredundant In Vivo Functions of TNF Produced by T Cells and Macrophages/Neutrophils

Abstract: Tumor necrosis factor (TNF, TNFalpha) is implicated in various pathophysiological processes and can be either protective, as in host defense, or deleterious, as in autoimmunity or toxic shock. To uncover the in vivo functions of TNF produced by different cell types, we generated mice with TNF ablation targeted to various leukocyte subsets. Systemic TNF in response to lipopolysaccharide was produced mainly by macrophages and neutrophils. This source of TNF was indispensable for resistance to an intracellular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
248
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 228 publications
(257 citation statements)
references
References 58 publications
8
248
1
Order By: Relevance
“…Our results are consistent with a recent report that showed an important role for T cell-derived TNF-␣, which found that TNF-␣ knocked out in the T cell lineage resulted in increased susceptibility to LM challenge, as well as inability to control bacterial load by day 4 p.i. (43). Moreover, our results are consistent with the implication that T cell-derived TNF-␣ possesses a distinct function in host defense by providing protection against high bacterial load (43), constituting a second line of defense.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with a recent report that showed an important role for T cell-derived TNF-␣, which found that TNF-␣ knocked out in the T cell lineage resulted in increased susceptibility to LM challenge, as well as inability to control bacterial load by day 4 p.i. (43). Moreover, our results are consistent with the implication that T cell-derived TNF-␣ possesses a distinct function in host defense by providing protection against high bacterial load (43), constituting a second line of defense.…”
Section: Discussionsupporting
confidence: 90%
“…We previously established that the cholinergic antiinflammatory pathway regulates TNF production in the spleen (12), but the cellular source of spleen TNF during endotoxemia was previously unknown. Macrophages, a component of the reticuloendothelial system, are a major source of TNF in endotoxemia (18). TNF was detected by immunofluorescence 30 min after endotoxin administration in the red pulp and the marginal zone (MZ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Furthermore, TNF derived from hematopoietic cells, especially macrophages/neutrophils, plays a critical role in inflammatory reactions 20,33 and Listeria infection. 34 For mycobacterial infection a partial protective effect has been shown by membrane TNF in the same noncleavable membrane TNF mouse 35 and in a different transgenic mouse model. 13 The partial protection generated in mem-TNF mice could indicate local cell-to-cell TNF signaling by membrane-expressed TNF on T cells or macrophages at the site of infection, leading to a partial activation of the immune cells.…”
Section: Discussionmentioning
confidence: 99%